Branching pattern of marginal mandibular nerve-an anatomical study - Dar, Showkat Ahmad; Shahdad, Shaheen; Khan, Javed Ahmad; Nisa, Gousia; Jan, Neelofar; Samoon, Sayma (International Journal of Research in Medical Sciences, 2018)
Background: Marginal Mandibular nerve, a branch of facial nerve, emerges at the lower part of the anterior border of parotid gland. It supplies risorius, muscles of lower lip and chin and joins mental nerve. This nerve has an important relationship with the lower border of mandible and is likely to be damaged during procedures in or around the submandibular area and can lead to certain morbid conditions like deviation of angle of mouth, drooling of saliva and difficulty in phonation. Methods: Sixty formalin preserved specimens of head and neck were used for studying the branching pattern of marginal mandibular nerve. The present study was conducted in the department of Anatomy Govt Medical College Srinagar over a period of two and a half years from 2015 to 2017. Cadaveric dissection was also used in the study during the routine teaching of undergraduate MBBS and BDS students in the department. The photographs of the variations seen during the study were taken. Results: In Forty-seven specimens (78.33%) there was a single branch of marginal mandibular nerve, in 10 specimens (16.6%) there were two branches of marginal mandibular nerve and in three specimens (5.0%) the marginal mandibular nerve was having three branches. Conclusions: From the above study it was concluded that marginal mandibular nerve can have two or three branches. Therefore, it is advisable to take due care during surgical procedures in the lower part of face and upper part of neck to preserve marginal mandibular nerve and to ensure cosmesis and prevent morbidity.